MOTOR CONVENTIONAL INSURANCE; ITS PREFERENCE AMONG MUSLIMS IN PETALING JAYA - Muhammad Amsyar Arshad,; Ruhaizah Abdul Ghani, (Journal of Islamic, Social, Economics and Development, 2022)
Motor insurance, whether convetional or Islamic one, is a part and parcel of buyingvehicles as to cover certain cost for the damage that might occurs in any incidents as well asthe cost for the treatment of certain injuries. This study will explore the Muslims preference onconventional insurance as well as further investigate the determinant factors of Muslims’preference. As an explorative study, the research used qualitative method by interviewingrespondents among Muslims in Petaling Jaya as to get the data. As a result, the datademonstrated that the determinant factors are lack of awareness on takaful and inefficient rolesof agent in promoting the product. Thus, the researcher suggests that Takaful agencies to putextra effort in advertising, marketing and merging with vehicle companies.